Comparison of erythropoietin resistance in hemodialysis patients using calcitriol, cinacalcet, or paricalcitol. (14th July 2015) - Afsar, Baris; Agca, Erhan; Turk, Suleyman
Abstract The erythropoiesis‐stimulating agent (ESA) hyporesponsiveness index (EHRI) calculated as the weekly dose of EPO divided by weight (kg) divided by hemoglobin level (g/dL) has been considered useful to assess ESA resistance. Recent evidence suggests that active vitamin D, cinacalcet, and paricalcitol use may be related with lower ESA resistance. We conducted this observational cross‐sectional study to investigate ESA resistance calculated by the EHRI among patients using calcitriol, cinacalcet, and paricalcitol. Participants underwent a medical history taken, physical examination, measurement of biochemical analysis, calculation of dialysis adequacy, and EHRI. Sixty‐five patients did not receive any treatment regarding vitamin D, paricalcitol, and cinacalcet (group 1), 41 were taking only vitamin D (group 2), 50 were taking only paricalcitol (group 3), 19 were taking only cinacalcet (group 4), and 21 were taking paricalcitol + cinacalcet (group 5). The EHRI values for groups 1, 2, 3, 4, and 5 were 11.36 ± 8.72, 11.58 ± 5.72, 8.29 ± 5.54, 9.49 ± 4.61, and 8.91 ± 4.44 respectively (P =.034). Post hoc analysis showed that the EHRI differed between group 1 and group 3 (P =.017) and between group 2 and group 3 (P =.006). In linear regression analysis, use of paricalcitol was independently associated with EHRI. In conclusion, paricalcitol use was associated with lower EHRI levels as a measure of ESA resistance.